2022
DOI: 10.1136/rmdopen-2021-002050
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of SARS-CoV-2 vaccination in patients with rheumatoid arthritis (RA) on DMARDs: as determined by antibody and T cell responses

Abstract: ObjectivesTo assess antibody and T cell responses to SARS-CoV-2 vaccination in patients with rheumatoid arthritis (RA) on disease-modifying antirheumatic drugs (DMARDs).MethodsThis prospective study recruited 100 patients with RA on a variety of DMARDs for antibody and T cell analysis, pre-vaccination and 4 weeks post-vaccination. Positive antibody response was defined as sera IgG binding to ≥1 antigen. Those that remained seronegative after first vaccination were retested 4 weeks after second vaccination; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 15 publications
(14 reference statements)
2
19
0
Order By: Relevance
“…We confirm that T cell response to COVID-19 vaccine is defective among ISD patients receiving DMT as reported in MS and rheumatoid arthritis (RA) [ 22 ]. Anti-CD20 mAb most likely affects the humoral anti-Spike response but has no strong effect on the T cell response [ 22 ]. From our knowledge, our study is the first to incriminate GC as the main DMT to dampen the T cell response against Spike, and such an effect is observed both following COVID-19 vaccine and infection.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We confirm that T cell response to COVID-19 vaccine is defective among ISD patients receiving DMT as reported in MS and rheumatoid arthritis (RA) [ 22 ]. Anti-CD20 mAb most likely affects the humoral anti-Spike response but has no strong effect on the T cell response [ 22 ]. From our knowledge, our study is the first to incriminate GC as the main DMT to dampen the T cell response against Spike, and such an effect is observed both following COVID-19 vaccine and infection.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, T cell responses on GC treated patients have been described only in small cohorts of patients. T cell exploration was limited to ISD patients showing a defective humoral response or after the exclusion of previously SARS-Cov2 infected patients [ 5 , 11 , 21 , 22 ]. We confirm that T cell response to COVID-19 vaccine is defective among ISD patients receiving DMT as reported in MS and rheumatoid arthritis (RA) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 ABT also binds to CD80/86 expressed on B cells and inhibits antibody production, 22 , 23 which means that ABT can affect humoral immune responses both directly and indirectly. These mechanisms may result in the reduced immunogenicity of vaccines such as pneumococcal, 24 influenza, 25 and SARS-CoV-2 mRNA vaccines 26 for patients undergoing treatment with ABT. As previously reported, in our short- and medium-term observations, patients undergoing treatment with ABT had lower adjusted NAb titers than HCs.…”
Section: Discussionmentioning
confidence: 99%
“…While longitudinal studies in SARS-CoV-2 convalescent and vaccinated individuals have revealed the dynamics of humoral and cellular immune responses in healthy individuals, data on long-term vaccine-induced immune responses in patients with rheumatic diseases are still scarce 3–5. Two doses of mRNA-based anti-SARS-CoV-2 vaccines result in durable SARS-CoV-2 antibody binding that correlate to potent neutralisation responses in healthy volunteers 6 7. Most patients with rheumatic diseases seroconvert following mRNA vaccination but anti-S titres may develop with a delayed kinetic and lower magnitude compared with healthy controls (HCs) depending on the immunomodulatory therapies used 8–10…”
Section: Introductionmentioning
confidence: 99%